Urinary incontinence rehabilitation of after radical prostatectomy: a systematic review and network meta-analysis - Yu, Kai; Bu, Fan; Jian, Tengteng; Liu, Zejun; Hu, Rui; Chen, Sunmeng; Lu, Ji (Frontiers in Oncology, 2024)
Abstract: Purpose: To provide treatment for patients with urinary incontinence at different periods after radical prostatectomy. Methods: The PubMed, Embase, Cochrane and Web of science were searched for all literature on the effectiveness on urinary control after radical prostate cancer between the date of database creation and 15 November 2023 and performed a quality assessment. A network meta-analysis was performed using RevMan 5.3, stata17.0 software and evaluated using the surface under the cumulative ranking curve (SUCRA). Results: The results of the network meta-analysis showed that: pelvic floor muscle therapy including biofeedback with professional therapist guided treatment demonstrated better results at one month to six months; electrical stimulation, biofeedback, and professional therapist guidance may be more effective at three months of treatment; professional therapist-guided recovery may be less effective at six months of treatment; and combined therapy demonstrated better results at one year of treatment. During the course of treatment, biofeedback with professional therapist guided treatment may have significant therapeutic effects in the short term after surgery, but in the long term, the combination of multiple treatments (Pelvic floor muscle training+ Routine care+ Biofeedback+ Professional therapist guided treatment+ Electrical nerve stimulation therapy) may address cases of urinary incontinence that remain unrecovered long after surgery. Conclusion: In general, all treatment methods improve the different stages of functional recovery of the pelvic floor muscles. However, in the long term, there are no significant differences between the treatments. Given cost-effectiveness, Pelvic floor muscle training+ Routine care+ Biofeedback+ Professional therapist guided treatment+ Electrical nerve stimulation therapy within 3 months and Pelvic floor muscle+ Routine care after 3 months may be a more economical option to treat urinary incontinence.